Optimization of Level of Incorporation of Different Dietary Fiber in the Development of Spent Hen Meat Snack Sticks - Choubey, V.; Tomar, S.; Yadav, S.; Gupta, B.; Khare, A.; Singh, P. K.; Meshram, S.; Dixit, B. (International Journal of Bio-resource and Stress Management, 2024)
The study was conducted from October to December, 2021 in the Department of Livestock Products Technology, College of Veterinary Science, Jabalpur, Madhya Pradesh, India to prepare spent hen meat snack sticks (SHSS) by partially replacing rice flour (RF) from the product formulation with healthy, dietary fiber rich oat, finger millet and amaranth flours (OF, FMF and AF) at different levels. Four batches of SHSS were prepared by substituting RF with different levels of OF, FMF and AF each at 0%, 5%, 10% and 15%. The optimum level of incorporation of dietary fiber from each set of products was standardized based on sensory evaluation of SHSS for various attributes. A combination of steaming, drying and frying (170°C for 45 sec) was found to be the most suitable cooking method for SHSS. Substitution of RF with 15% OF resulted in a significant decrease in flavour, crispness, and overall acceptability of the snacks while lower levels did not affect the sensorial attributes. FMF at 5% level did not alter the sensory attributes while at higher levels of replacement a significant decrease in color, flavor, crispness, and overall acceptability scores were noted. Higher levels of AF (15%) significantly improved flavour and overall acceptability of SHSS. The study clearly revealed that OF (10%), FMF (5%) and AF (15%) can be used efficiently for substitution of RF in the formulation of healthier and sensorially acceptable products. Snacks crafted with spent hen meat and dietary fiber will enhance the nutritional value especially with respect to amino acids, flavour, taste and technological functionality.